2022
DOI: 10.1177/87569728211070225
|View full text |Cite
|
Sign up to set email alerts
|

Digital Technologies in Built Environment Projects: Review and Future Directions

Abstract: Through a systematic literature review we explore how digital technologies reshape and catalyze digital innovations in the built environment—a highly project-based setting. We analyzed circa 3,000 titles, further narrowed down to 87 articles. We synthesized an original framework for data analysis. The article presents implications for the deployment of digital technologies on three levels: individuals, organizations, and projects. Whereas most of these studies examined the impact of digital innovation in proje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 100 publications
0
15
0
1
Order By: Relevance
“…Discussions on blockchain in construction have accelerated after 2015, a decade after the first introduction of blockchain in 2008. As construction is very transaction-heavy, it offers an ideal setting for blockchain innovation as it becomes increasingly digitalised (Papadonikolaki et al, 2022). Reports show the increasing popularity of blockchain that is touted as the next frontier in construction (Li et al, 2019;Hunhevicz and Hall, 2020;Perera et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Discussions on blockchain in construction have accelerated after 2015, a decade after the first introduction of blockchain in 2008. As construction is very transaction-heavy, it offers an ideal setting for blockchain innovation as it becomes increasingly digitalised (Papadonikolaki et al, 2022). Reports show the increasing popularity of blockchain that is touted as the next frontier in construction (Li et al, 2019;Hunhevicz and Hall, 2020;Perera et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Discussions on blockchain in construction have accelerated after 2015, a decade after the first introduction of blockchain in 2008. As construction is very transaction-heavy, it offers an ideal setting for blockchain innovation as it becomes increasingly digitalised (Papadonikolaki et al. , 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The construction industry is one of the industries or sectors attributed to the least adoption of industry 4.0 technologies, while IT and technology and telecommunication lead the digital maturity in terms of adoption (Kane et al, 2015). On the other hand, Papadonikolaki et al (2022) reviewed the frequency of digital innovations across data and found that BIM is the most adopted digital innovation. Even in systematic literature reviews of papers on construction 4.0, BIM has drawn much attention in practical publications (Oesterreich and Teuteberg, 2016).…”
Section: Stakeholders' Perceptionmentioning
confidence: 99%
“…Among the industry 4.0 related tools and technologies, most of the studies and use cases focused on BIM implementation (Heaton et al, 2019;Papadonikolaki et al, 2022;Wen et al, 2021). Furthermore, many studies focus on BIM adoption in diverse contexts (Hajj et al, 2021;Murguia et al, 2021;Papadonikolaki, 2017).…”
Section: Studies On Individual Technologiesmentioning
confidence: 99%
“…Larjovuori et al (2016) defined DL as "the leaders' ability to create a clear and meaningful vision for the digitalization process and the capability to execute strategies to actualize it". DL unlike traditional leadership are built according to environment of the organisations' in (Morgan and Papadonikolaki, 2022), and when built appropriately, DL will facilitate innovation performance (Benitez et al, 2022), governance (Seaman, 2021), agility and transformation (Stepnov, 2021), self-organisation (Gierlich-Joas, Hess, and Neuburger, 2020), cultural intelligence (Ruth and Netzer, 2020), collaboration (Frankowska and Rzeczycki, 2020), and psychological well-being (Zeike et al, 2019).…”
Section: Digital Leadership (Dl)mentioning
confidence: 99%